Association of methylenetetrahydrofolate reductase C677T and reduced-f carrier-1 G80A gene polymorphism with preeclampsia in Sudanese women. (2nd April 2020) - Ahmed, Sumia F.; Ali, Mohamed M.; Kheiri, Sumeya; Elzaki, Salah Eldin G.; Adam, Ishag
ABSTRACT: Purpose: To assess the associations between preeclampsia, methylenetetrahydrofolate reductase ( MTHFR ) C677T, and reduced folate carrier-1 ( RFC-1 ) G80A gene polymorphism in Sudanese women. Methods: A matched (for age and parity) case–control study was conducted in a tertiary hospital (Saad Abualila) in Khartoum, Sudan during February to September 2018. The cases were women with preeclampsia and healthy pregnant women were the controls (160 women in each arm of the study). Genotyping for MTHFR C677T and RFC-1 G80A was performed by polymerase chain reaction–restriction fragment length polymorphism. Results: . . The MTHFR C677T variation was significantly more frequent in women with preeclampsia (16.2%) than in healthy pregnant women (1.8%) (OR = 10.1, 95% CI = 3.0–34.2, P < 0.001). There was borderline significance in the RFC-1 G80A variation, which was present in 2.50% of women with preeclampsia, but was not found in healthy pregnant women ( P = 0.052). Conclusion: s: A higher prevalence of MTHFR C677T polymorphism in women with preeclampsia compared with healthy pregnant women suggests involvement of this variation in preeclampsia in Sudan.